Implementation of Sustainable Holistic-Integrative Early Childhood Education (PAUD HI) Post UNICEF Assistance - Sonbai, Eflin I.; Waluyo, Edi (LPPM Undiksha, 2025)
Integrative Holistic Early Childhood Education (PAUD HI) is a development for early childhood that aims to meet the essential needs of children. The PAUD HI program has been implemented in many PAUD institutions in Indonesia. However, its implementation still faces various obstacles, and it is necessary to measure the role of stakeholders so that it can project the sustainability of PAUD HI in the TTS Regency. This study aims to compare the implementation of PAUD HI services, link the role of stakeholders in the implementation of PAUD HI, and project the program's sustainability after mentoring. The research method uses a mixed-method approach. The population in this study was 40 UNICEF-assisted Holistic Integrative PAUD institutions. Using purposive sampling techniques, samples were taken from 15 institutions, or around 50% of the population. Data collection methods used surveys, questionnaires, interviews, and documentation. Quantitative analysis was carried out descriptively, while qualitative analysis used data reduction, presentation, and conclusions. The study's results on quantitative data showed that education and welfare services achieved 100% achievement in all schools, but several indicators in health and protection services had 0% achievement. The care services showed 100% success in one indicator but low in the other three. The level of service achievement between HI PAUDs also varies, and this tends to be influenced by stakeholder support. The implications of this study indicate the importance of strengthening the capacity of local institutions and stakeholders in maintaining the program's sustainability.